Забезпечення міцності тонкостінних конструкцій шляхом обґрунтування параметрів із використанням апроксимацій поверхонь відгуку - Бондаренко, Марина Олександрівна (НТУ "ХПІ", 2018)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.02.09 – динаміка та міцність машин. Національний технічний університет "Харківський політехнічний інститут", Міністерство освіти і науки України, Харків, 2018. Дисертація присвячена розробці підходу і моделей для забезпечення конструкційної міцності складних тонкостінних машинобудівних конструкцій, що працюють в умовах геометрично та фізично нелінійної поведінки матеріалу, шляхом обґрунтування проектних рішень. Розроблений підхід базується на використанні математичної моделі напружено-деформованого стану з урахуванням геометричної та фізичної нелінійностей, а також – методів апроксимації для побудови функцій, що описують оцінювані характеристики досліджуваного об'єкта. Різні критерії, за якими проводиться пошук проектних рішень (включаючи характеристики міцності, жорсткості, технологічні та економічні чинники), вносяться до цільової функції. У процесі пошуку проектних рішень запропоновано послідовно використовувати апроксимаційні моделі різного ступеня точності. До них застосовується розроблений алгоритм пошуку раціональних параметрів, який враховує особливості форми поверхонь відгуку, що спостерігаються при розв'язанні прикладних задач. Розроблені алгоритми і моделі застосовані для розв'язання тестових та прикладних задач. Зокрема, розроблені рекомендації для каркасу кузова автобуса, вантажного напіввагона, каркасу кабіни трактора, корпусів БТР-80 та тягача МТ-Л. Проведена розрахунково-експериментальна верифікація розроблених скінченно-елементних моделей.

The thesis in qualification for a scientific degree of Candidate of Technical Science in speciality 05.02.09 ‒ dynamics and strength of machines, National Technical University "Kharkiv Polytechnical Institute", Kharkiv, 2018. The dissertation deals with the development of approach and models for providing of structural strength of complicated thin-walled machine-building structures, which operate in the conditions of geometric and physical nonlinearities using design solution validation. The developed approach is based on the use of mathematical model for stress-strain state taking into account geometric and physical nonlinearities and methods of approximation for constructing functions describing the evaluated characteristics of the object under study. The various factors behind the search for design solutions (including characteristics of strength, rigidity, technological and economic factors), are being added into this function. During searching for design solutions it is proposed to successively use approximation models of various accuracy degrees. The developed algorithm for rational parameters search, which takes into account the peculiarities of the response surface shape observed in solving applied problems, is applied to them. In this case, the solution is sought over the whole range of parameter changes. Thus, in the search process, global trends of changes in design decisions are taken into account, and not local ones, as in other approaches. This allows obtain a rational solution that is stable to changes in parameters, which are possible in course of design work and production conditions. The developed algorithms and models are used for solving test and applied problems. In particular, recommendations for the body framing of the bus, freight car, the frame of the tractor cabin, the BTR-80 and MT-L hulls are developed. Computational and experimental verification of developed finite-element models was carried out. The research was carried out at three objects: on the upper part of BTR-80 armored personnel carrier mock-up, and on the prototypes of BTR-3E hull and covered railcar. During frequency characteristics studies, the oscillations excitation of the hull mock-up was effected by rubberized drummer influence at certain points of structure. With use of verified finite element models, the BTR-3E hull prototype was investigated. The experimental research technique provided impulsive action on the hull at a number of points, and fixation of time distributions of accelerations at these points by accelerometers. The results difference is in range of 8-12% for frequencies of free oscillations and for damping logarithmic decrement. Computational studies, and then full-scale tests are also subject to the covered railcar prototype made with recommended settings. Average difference for displacement and stress is 15%.
Thin-walled structures strength assurance by parameters validation using response surfaces approximations
Keywords: прикладна теорія пружності; міцність машин; напружено-деформований стан; тонкостінна машинобудівна конструкція; геометрична нелінійність; фізична нелінійність; метод скінченних елементів; метод скінченних різниць; поверхня відгуку; апроксимація; автореферат дисертації; applied theory of elasticity; strength of machines; deformed state; thinwalled mechanical engineering structure; geometric nonlinearity; physical nonlinearity; finite element method; finite difference method; response surface; approximation; 539.3